The Evolution of Islamic Monetary Policy: Civilizational Roots, Legal Foundations, and Contemporary Relevance - Rosadi, Imron; Janwari, Yadi; Al-Hakim, Sofian (Yayasan Mentari Madani, 2026)
This study investigates the dynamic evolution of monetary policy within Islamic civilization, spanning from the Prophetic era to the late Ottoman Empire. Contrary to static legalistic narratives, this research employs a historical-comparative approach to demonstrate that Islamic monetary practices were highly adaptive responses to shifting economic realities, ranging from cross-border trade integration to global inflationary shocks. The analysis highlights several pivotal shifts: the pragmatic adoption of foreign currency during the Rashidun Caliphate, the assertion of monetary sovereignty through the Arabization of coinage under the Umayyads, and the development of sophisticated credit instruments during the Abbasid era. Furthermore, the study critically examines the failures of fiat money experiments in the Mamluk Dynasty and the Delhi Sultanate, contrasting them with the relative stability of the Fatimid gold standard and the Ottoman Empire's strategic adaptation to the “Price Revolution.” By synthesizing data from numismatic evidence and classical texts—such as those by Al-Maqrizi and Ibn Khaldun—with modern economic historiography, this article argues that the resilience of an Islamic monetary system depends less on the intrinsic material of the currency (gold/silver) than on institutional integrity, state credibility, and market supervision (Hisbah). These historical insights provide a vital empirical foundation for formulating contemporary Islamic economic policies, particularly regarding fiscal-monetary integration and currency stability management.